PENGARUH WAKTU PROSES THERMAL SPRAY ALUMINIUM TERHADAP LAJU KOROSI DAN STRUKTUR MORFOLOGI BAJA AISI 1020 - Dedek Arya Pangestu; Sri Hastuti; Catur Pramono; Nurhadi; Ahmad Nurdin; Bramono Pandupradityo (MACHINERY Jurnal Teknologi Terapan, 2024)
Thermal spray aluminum is one type of engineering technology in coating. The main property that indicates the quality of the thermal spray result is resistance to corrosion. Thickness, composition, and morphological structure are very influential things about the rate of corrosion. The long parameters of spraying in the aluminum thermal spray process will affect the corrosion rate, thickness, morphological structure, and coating composition. The aim of this study is to analyze the influence of spraying time on corrosion rate and morphological structure of coating layer in AISI 1020 steel. The types of tests performed are corrosion rate testing, Scanning Electron Microscope (SEM), Energy Dispersive Spectroscopy (EDS). The study used an experimental thermal spray method using time variations of 5 seconds, 10 seconds, and 15 seconds. The results of the study showed that values of corrosion rate, thickness and morphological structure of the coating are best present in spraying using a time of 15 seconds.